Rancang Bangun Real Count E-voting Menggunakan Mikrokontroler - Inge Frastika Fitri; Derisma (CHIPSET, 2020)
The purpose of this research is to implement an embeded system in a form of a device that can provide e-voting services and a realcount process that can quickly accumulate votes. With this device, it is expected to be a solution to conventional elections that are still prone to fraud, wasteful costs, and inefficient. This device applies NFC technology. Voter’s idcard is used as an identifier, the UID of voter’s idcard is read by the NFC reader and the verification process is running. Voters are entitled to vote if the voters' idcard number is verified and registered in the database. Here the voter will be allowed to proceed for choosing their preferred candidate from the pushbuttons. This device is expected to be saved huge cost by using pushbuttons instead of ballot papers. This device uses the SIM808 module as a data communication medium to send http packages containing uid and vote values to the webserver, to be further matched in a table in the database. When voters vote, the uid of the voter is stored in the results table in the following database with the value of the vote, and if an idcard with the same uid votes again, then the latest vote values will not be store. This method prevents duplication which often happens in conventional voting system. After whole voting ends, the final result is displayed on a web page in a graphical view for the satisfaction of voters. Voting and counting has become much faster and easier as the system doesn't really require counting personnel, therefore there has been a substantial reduction in the number of remuneration that is paid to them. This result menu can only be accessed after the specified time.